Miss Julie (Criterion Collection/Janus Films, 1951)
Swedish filmmaker Alf Sjoberg's visually innovative, Cannes Grand Prix-winning adaptation of August Strindberg's renowned 1888 play brings to scalding life the excoriating words of the stage's preeminent surveyor of all things rotten in the state of male-female relations.Miss Julievividly depicts the battle of the sexes and classes that ensues when a wealthy businessman's daughter (Anita Bjork, in a fiercely emotional performance) falls for her father's bitter servant.. Celebrated for its unique cinematic style (and censored upon its first release in the United States for its adult content), Sjoberg's film was an important turning point in Scandinavian cinema..